Comparison of pulmonary circulation parameters acquired by cardiovascular magnetic resonance with right heart catheterization and transthoracic echocardiography in patients with recent-onset dilated cardiomyopathy - Lukáš Opatřil; Mary Luz Mojica-Pisciotti; Roman Panovský; Jan Máchal; Tomáš Holeček; Věra Feitová; Július Godava; Hana Poloczková; Vladimír Kincl; Michael Andrej; Jan Krejčí (PLoS ONE, 2026)
Introduction Evaluating pulmonary circulation parameters (PCP) with cardiovascular magnetic resonance (CMR) is a relatively new approach with the potential for complex evaluation of the cardio-pulmonary system. Its impact might complement clinical assessment through right heart catheterization (RHC), the gold standard in evaluating pulmonary hypertension (PH) and hemodynamics, and transthoracic echocardiography (TTE). The study aims to examine the correlation between PCP and diastolic and systolic function, as well as PH, in patients with recent-onset dilated cardiomyopathy (RODCM). Methods Eighty-four patients with RODCM were retrospectively included. All patients had a CMR examination, RHC (including pulmonary capillary wedge pressure (PCWP) and pulmonary vascular resistance (PVR)), and TTE. The pulmonary transit time (PTT), corrected pulmonary transit time (PTTc), systolic and diastolic function, and PH were assessed. Patients were divided into groups according to the PH and the diastolic function. Results PTT and PTTc correlated with PCWP, cardiac index, PVR, and E/e’. Patients with a restrictive filling pattern showed significantly longer PTT. The receiver operating characteristic curves for PTT, PTTc, and PH were assessed with areas under the curve of 72.7% for PTT and 75.3% for PTTc, and cut-off values of 8.62 s (PTT) and 8.52 s (PTTc). Conclusion To our knowledge, this is the first study focused on CMR-derived PCP in an RODCM group. Our findings show that PTT and PTTc are prolonged in patients with impaired systolic and diastolic function, and PH. Therefore, PCP might offer critical information to evaluate the cardio-pulmonary system comprehensively.